Time Trends and Income Inequalities in Cancer Incidence and Cancer-Free Life Expectancy – a Cancer Site-Specific Analysis of German Health Insurance Data - Tetzlaff, Fabian; Hoebel, Jens; Epping, Jelena; Geyer, Siegfried; Golpon, Heiko; Tetzlaff, Juliane (Frontiers in Oncology, 2022)
Cancer represents a major burden of morbidity and mortality globally. So far, however, little is known on time trends and inequalities in the lengths of life spent free of any cancer. This study steps into this gap by analysing time trends and income inequalities in cancer-free life expectancy (CFLE). For this retrospective cohort study, data of a large German health insurer were used (N = 3,405,673individuals, 2006–2018). Income inequalities were assessed using individual income (<60% of German average income (GAI) and ≥60% of GAI). Trends in incidence risks were analysed employing proportional-hazard regression models by splitting the observation time into three periods of 52 months. Trends in CFLE in total and for the most common site-specific cancers were calculated based on multiple decrement life tables. Incidence rates declined in almost all cancers and CFLE increased substantially over time (49.1 (95% CI 48.8-49.4) to 51.9 (95% CI 51.6-52.2) years for men, 53.1 (95% CI 52.7-53.5) to 55.4 (95% CI 55.1-55.8) years for women at age 20 for total cancer) and income groups. Considerable income inequalities in cancer risks were evident in both sexes, but were more pronounced in men (total cancer HR 0.86 (95% CI 0.85-0.87)), with higher-income individuals having lower risks. The highest income inequalities were found in colon (HR 0.90 (95% CI 0.87-0.93)), stomach (HR 0.78 (95% CI 0.73-0.84)), and lung cancer (HR 0.58 (95% CI 0.56-0.60)) in men. A reverse gradient was found for skin (HR 1.39 (95% CI 1.30-1.47) men; HR 1.27 (95% CI 1.20-1.35) women) and prostate cancer (HR 1.13 (95% CI 1.11-1.15)). The proportion of CFLE in total life expectancy declined for lung, skin and cervical cancer in women, indicating a relative shortening of lifetime spent cancer-free. In contrast, increasing proportions were found in breast and prostate cancer. To our knowledge, this is the first study analysing trends and income inequalities in CFLE. The life span free of cancer increased clearly over time. However, not all cancer types contributed equally to this positive development. Income inequalities persisted or tended to widen, which underlines the need for increased public health efforts in socioeconomically vulnerable groups.